PENGARUH ENVIRONMENTAL (LINGKUNGAN), SOCIAL (SOSIAL), DAN GOVERNANCE (TATA KELOLA) DISCLOSURE TERHADAP NILAI PERUSAHAAN YANG TERDAFTAR DI INDEKS ESG LEADERS PERIODE 2019-2023 - Laelatun Mazaya; Nurlaeli, Fenti; Garnis Setia Rahmadhaniar (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2025)
The importance of ESG Disclosure for companies is not only to attract investors but also to form corporate responsibility in overcoming the impacts that arise due to the company's performance both in terms of environment, social and governance. This research aims to determine the influence of Environmental, Social and Governance Disclosure on the Value of Companies listed on the ESG Leaders Index for the period 2019 - 2023. This type of research is quantitative research with secondary data. The number of samples in this research was 8 companies using a purposive sampling method. The data analysis method used in this research is the Inner Model Test. The research results show that Environmental, Social and Governance Disclosures have no effect on Company Value.